Same same but different: regional coherence between institutions and policies in family firm succession - Lenz, Regina; Glückler, Johannes (European planning studies, 2020)
Family firms represent the backbone of regional economies in Europe. Yet, due to demographic and societal changes, family firm succession increasingly poses a challenge to both firm continuity and regional stability, which is why policymakers look for appropriate ways to support family firms in their succession processes. In pursuit of policies that fit local institutional conditions, we explore the fact that two structurally similar European regions facing the same succession problem have developed different policies to address it. Using the analytical framework of institutional logics and drawing on 67 interviews with family firms and succession experts in the Spanish Basque Country and the German region of Baden-Württemberg, we find that the different policies are coherent with each region’s unique constellation of the institutional logics of business, family, and community and thus make up distinct regional policy regimes. The paper offers a framework applicable to other regions for making underlying normative behavioural guidelines visible, and for more precisely assessing the relationship between institutions and policies. It contributes to a better understanding of the regional specificity of institutions as a base upon which place-sensitive policies can be developed, or fundamental attempts be made to re-shape institutions by political measures.